Fabrication, characterisation and CO2/N2 gas permeance study of novel blended membrane. (2015) - Farrukh, Sarah; Minhas, Fozia T.; Hussain, Arshad; Mujahid, Muhammad
The CO2 gas is the primary green house gas, which is the main cause of global warming. To capture CO2 gas, it is important to study the permeance behaviour of CO2 and N2 gases from different membranes. In this work, 5, 11, 17, 23-Tetra-tert-butyl-25, 27-bis-(2-piprazinoethyl)-26-dihydroxycalix[4]arene (CLP) was blended into cellulose acetate (CA) membrane to be used for gas permeation. Diffusion induced phase separation (DIPS) method was applied to fabricate membranes. The CA/CLP membranes were fabricated by varying concentration of CLP with respect to CA at 10wt%, 20wt%, 30wt% and 40wt%. The prepared membranes were characterised via Fourier transform infra red (FTIR) spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). CO2 and N2 gases were used for the gas permeation experiments. The increasing trend was observed in permeance of N2 gas as compared to CO2 gas for CA-CLP blended membranes.